Analisis Penggunaan Media Puzzle Dalam Pembelajaran Pendidikan Agama Islam - Dion Permana; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2023)
Islamic Religious Education has an important role in education, one of which is at the elementary school level, but in fact the interest and motivation of students in primary school learning in PAI learning at SDN 04 Talago is still low, so variations are needed in the learning process. The solution presented is the use of learning media. The type of media used by one of the PAI teachers at SDN 04 Talago Lubuk Attitude is puzzle media. This study aims to determine the use of puzzle media in PAI learning. This study uses a qualitative method with a case study research type. The results of the study reveal that the use of puzzle media in PAI learning is able to foster interest and motivation in student learning so that it can improve learning outcomes according to what is expected.